Effect of particulate matter exposure on the prevalence of allergic rhinitis in children: A systematic review and meta-analysis. (April 2021) - Lin, Lisen; Li, Tianyu; Sun, Mengqi; Liang, Qingqing; Ma, Yuexiao; Wang, Fenghong; Duan, Junchao; Sun, Zhiwei
Abstract: Among various air pollutants, particulate matter (PM) is the most harmful and representative pollutant. At the same time, allergic rhinitis (AR) is getting more and more attention, so we explore the relationship between PM and the prevalence of AR among children. Then, PubMed, Web of Science, Google Scholar was used to search for relevant studies up to January 2020. Literature quality assessment was processed using the Newcastle-Ottawa Scale (NOS) evaluation scale. Adjusted odds ratio (OR) with corresponding 95% confidence interval (CI) was retrieved from individual studies and pooled to generate a summary effect via STATA software. Besides, we test the result stability by Egger's test and funnel plot, and using the trim-and-fill method to modify the possible asymmetric funnel graph. 21 studies were included in the meta-analysis. 9 articles reported about PM2.5 on childhood AR (1.09, 95%CI: 1.01, 1.17, per 10 μg/m 3 increase). 15 articles reported about PM10 on childhood AR (1.06, 95%CI: 1.02, 1.11, per 10 μg/m 3 increase), PM2.5 exposure has a bigger effect on children AR than PM10 . In addition, a series of subgroup analysis was performed, and we found that PM2.5 and PM10 have different performances in different subgroups. In addition to this, we analyzed the sources of heterogeneity of the study. Apart from the results we got all have good stability without publication bias. Therefore, it can be concluded that exposure to PM may increase the prevalence of AR among children. Graphical abstract: Image 1 Highlights: PM2.5 causes more allergic rhinitis (AR) in children than PM10 . PM may contribute to the increase morbidity of AR among children. Children with AR should be specially protected from PM exposure.